SMS door security / Muhammad Hanif Mat Nasir, Muhammad Hafizuddin Mohd Tahar and Nabilah Mohd Hassan - Mat Nasir, Muhammad Hanif; Mohd Tahar, Muhammad Hafizuddin; Mohd Hassan, Nabilah (2013)
SMS Door Security is typically built to avoid any burglary from happening to your house with high security door type. With these device existents, it will become the informer and the first level safety to the house. In other words, it will reduce the chance of our house from being robbed. Furthermore SMS system using GSM will send the information to the house owner and nearby police station if there are any trials to breaking the house. It is also equip with the alarm to trigger if there are any intruder. This is to make sure the neighbor know if there any break-in the house. Other than that, with the use of keypad, the house owner doesn’t need to worry about the house key. They can leave their house with a relief. Maybe our creation not exactly safe, this is the other initiative to make our house safer than usual.